ALGORITHM COLLECTION OF TEXT DATA IN THE KAZAKH LANGUAGE - Rakhimova Д.Р.; Satybaldiev А.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This work is devoted to the creation of a system for the automatic collection and processing of open data in Kazakh from Internet resources, and bears practical significance in the tasks of collecting and analyzing text. The introduction substantiates the relevance of the chosen topic, a review of existing approaches, formulates the objectives of the study. We consider such a problem as the collection and primary processing of text data with subsequent analysis. Data collection is a priority, since open data from Internet resources is not structured and needs to be processed. The authors provide a system for processing web pages of Kazakh-language portals, and also gives practical application of this approach to real data of open resources using the created system. The approach of indexing documents using features is presented. The system will help structure open data from Internet resources, as well as analyze collected data. Practical results are presented